Adoption of cumin (Cuminum cyminum L.) production technology in arid zone of Rajasthan - Singh, Bhagwan (Journal of Spices and Aromatic Crops, 2005)
A study was conducted in four districts of Rajasthan, namely, Jodhpur, Pali, Bikaner and Jaisalmer, to determine the extent of adoption of various technologies in cumin (Cuminum cyminum) by farmers in the arid zone of the state. The study revealed that a majority (62.5%) of the farmers had adopted various production technologies to a medium level. Out of 16 variables, 5 variables, namely, education, occupation, irrigation facilities, sources of information and knowledge were positively and significantly correlated with overall adoption whereas, age and farming experience were negatively and significantly correlated with overall adoption of production technologies. The 16 independent variables taken together explained 59.9% of the variation in adoption of cumin production technology.